Kajian Literatur tentang Implementasi Akuntansi Berbasis Kinerja dalam Mewujudkan Good Financial Governance pada Pemerintah Daerah Provinsi Jawa Barat - Tommy Indra Gunawan; Dewi Noor Susanti (Journal of Innovative and Creativity, 2026)
The reform of regional public financial management has become an important issue in line with increasing demands for transparency, accountability, and performance in local governments. One strategic instrument considered capable of supporting sound financial governance is the implementation of performance-based accounting. This study aims to review and synthesize reputable literature on the implementation of performance-based accounting and its relationship with good financial governance in local governments, with a particular focus on the Government of West Java Province. This study employs a qualitative approach using a literature review method (narrative literature review). Data were obtained from reputable international journals, academic books, and reports published by international institutions relevant to public sector accounting and financial governance. The analysis was conducted through thematic analysis to identify key themes, patterns of relationships, and factors influencing the linkage between performance-based accounting and good financial governance. The findings indicate that performance-based accounting plays an important role in directing regional financial management toward the achievement of measurable outputs and outcomes, strengthening performance accountability, and improving the quality of financial information. Furthermore, the literature reveals a positive relationship between the implementation of performance-based accounting and the strengthening of good financial governance principles, particularly transparency and accountability. However, the effectiveness of performance-based accounting largely depends on supporting factors such as human resource capacity, leadership commitment, and the readiness of organizational systems and culture within local governments. The conclusion of this study emphasizes that performance-based accounting is a crucial instrument in achieving good financial governance in local governments; however, its successful implementation requires adequate institutional support. This literature review is expected to contribute theoretically to the development of public sector accounting literature and practically to serve as a reference for local governments in strengthening financial governance.